Knowledge and attitude about organ donation and transplantation among Omani university students - Alwahaibi, Nasar; Al Wahaibi, Anas; Al Abri, Mohammed (Frontiers in Public Health, 2023)
Background: Despite the importance of organ donation and transplantation in improving the quality of life, still, there is a shortage of organ donations, worldwide. Lack of knowledge among the public could be the reason. In previous studies, the focus was predominantly on medical students at universities. The aim of this study was to assess university students' knowledge and attitude about organ donation and transplantation among different colleges at the university. Method: A cross-sectional study was conducted among university students between August 2021 and February 2022 using a validated self-designed questionnaire. The questionnaire consisted of five sections. The first section was about the research information. The second section was informed consent. The third section was about sociodemographic information. The fourth section was about the knowledge of organ donation. The last section was about the attitude toward organ donation. The data were analyzed by descriptive statistics and chi-square tests. Results: The study included 2125 students. 68.1% were females, and 93.1% were in the age group 17-24 years old. Only 34.1% had good knowledge about organ donation, 70.2% had a low attitude, and 7.53% had adequate information about brain death. The most common reason for supporting donating organs among university students was to save a life (76.8%) and the most common reason for refusing organs, as I am still unaware. In addition, only 25.66% of the participants had a high attitude toward people with poor knowledge about organ donation. The majority of the students (84.13%) used online sources and social networks as the primary sources of information about organ donation. Conclusion: University students had a low level of knowledge and attitude toward organ donation and transplantation. The most common reason for supporting donating organs was to save a life; knowledge was the most important obstacle. Online sources and social networks were the primary sources of knowledge. Knowledge had a great impact on attitude. Campaigns, events, and students’ curricula would improve the university students' knowledge and attitude toward organ donation and transplantation.